2008
DOI: 10.1080/10401330802384862
|View full text |Cite
|
Sign up to set email alerts
|

Professional Boundaries: The Perspective of the Third Year Medical Student in Negotiating Three Boundary Challenges

Abstract: Our findings have implications for medical professionalism curricula, especially regarding the importance of mentorship and role modeling in medical education. Effective professional boundaries curricula allow the student to problem solve and practice communication skills in boundary challenging situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Instruments identified in the literature varied considerably dependent on purpose such as investigating prevalence (Bayer et al, 1996;Coverdale, Bayer, Chiang, Thornby, & Bangs, 1994) and various combinations of beliefs, behaviors, knowledge attitudes, skills, and ethics (Borys & Pope, 1989;Gaufberg et al, 2008;Jayaratne et al, 1997;White, 2003). No single instrument was found that could measure knowledge, comfort, experience, and ethical decision making.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Instruments identified in the literature varied considerably dependent on purpose such as investigating prevalence (Bayer et al, 1996;Coverdale, Bayer, Chiang, Thornby, & Bangs, 1994) and various combinations of beliefs, behaviors, knowledge attitudes, skills, and ethics (Borys & Pope, 1989;Gaufberg et al, 2008;Jayaratne et al, 1997;White, 2003). No single instrument was found that could measure knowledge, comfort, experience, and ethical decision making.…”
Section: Discussionmentioning
confidence: 96%
“…Forty-two 3rd-year Harvard medical students responded to an audiovisual presentation of three scenarios that focused on gift giving, self-disclosure, and running an errand for a supervisor (Gaufberg, Baumer, Hinrichs, & Krupat, 2008). The scenarios were selected based on real situations experienced by students in the previous year.…”
Section: Studies On Discipline-specific Practitioner/client Relationsmentioning
confidence: 99%
“…These settings represent prime opportunities to present information that will help prevent future boundary violations. 1,3,5 The AAMC suggests avenues for effective learning, including web modules, hands-on training sessions, expert case report consultations, and small-group discussions, all of which can include clinical reviews of circumstances with boundary questions. 1 Student education toward proper management of dual relationships is also facilitated through preceptor role modeling by practitioners attuned to such issues, especially in remote or culturally segregated areas where there are no alternative sources of health care.…”
Section: Teaching About Professional Boundaries In the Medical Schoolmentioning
confidence: 99%
“…4 Another survey assessed American medical students' attitudes about three boundary challenges: gift-giving, self-disclosure, and running personal errands for a supervisor. 5 Of these three, there were, in particular, significant differences in how students negotiated the prospect of running errands. Students who complied with a supervisor's request to run errands cited fear of damaging the relationship, appearing ungrateful, or negatively affecting future learning opportunities.…”
mentioning
confidence: 99%
See 1 more Smart Citation